Advancements in galactic chemical evolution - Fraser-Govil, J (2022)
In this thesis we examine several improvements which can be made to the canonical under- standing of Galactic Chemical Evolution (GCE) models in light of modern developments in stellar physics and new modelling techniques. Not only is GCE a vital component of our understanding of the history and composition of the universe in its own right, but since it incorporates physics on the scale of the cosmological to the subatomic, it may also be used as an independent probe and constraint on physics across many different fields.